Effectiveness of Intravitreal Bevacizumab (Avastin™) in Vitreous Hemorrhage Associated with Proliferative Diabetic Retinopathy - . Zarkesha; Sofia Iqbal; Muhammad Kamran Khalid; Muhammad Irfan Ullah (Pakistan Journal of Health Sciences, 2026)
Proliferative diabetic retinopathy (PDR) is a major cause of vision loss in diabetic patients. Vitreous haemorrhage (VH) is a common complication of PDR that significantly affects visual acuity. Intravitreal bevacizumab (Avastin™) has been used as a treatment option for VH associated with PDR. Objectives: To determine the effectiveness of intravitreal bevacizumab (Avastin™) in clearing vitreous haemorrhage and improving visual acuity in patients with PDR. Methods: This quasi-experimental study was conducted at the Ophthalmology Department, Hayatabad Medical Complex, Peshawar, from 01-01-2025 to 30-06-2025. A total of 79 patients with PDR-associated VH were included. Patients received three intravitreal bevacizumab injections at monthly intervals. Outcomes included VH clearance, improvement in best corrected visual acuity (BCVA), and requirement of pars plana vitrectomy. Data were analysed using SPSS version 22.0. Paired sample t-test and Chi-square test were applied, with p≤0.05 considered statistically significant. Results: The mean age of participants was 41.49 ± 10.54 years. VH clearance was observed in 67 (84.8%) patients, while improvement in BCVA occurred in 57 (72.2%) patients. Pars plana vitrectomy was required in 14 (17.7%) patients. Mean BCVA significantly improved from 0.81 ± 0.10 logMAR pre-therapy to 0.45 ± 0.24 logMAR post-therapy (p